Efficacy of a fixed combination of calcipotriol/betamethasone dipropionate topical gel in adult patients with mild to moderate psoriasis: blinded interim analysis of a phase IV, multicenter, randomized, controlled, prospective study. (26th October 2014) - Reich, K.; Zschocke, I.; Bachelez, H.; de Jong, E.M.G.J.; Gisondi, P.; Puig, L.; Warren, R.B.; Mrowietz, U.; the TTOP study group
Abstract Background Psoriasis is a common, chronic, inflammatory skin disease with the majority of individuals having limited disease, treated with topical medication. However, special attributes of topical treatments like galenic/cosmetic properties or an inconvenient treatment schedule may result in low preference for topical treatments. Hence, there is strong medical need for a topical medication, which is highly efficacious, easy‐to‐use and preferred by both physicians and patients. Objective Blinded interim analysis with the purpose to assess efficacy of (both from the physician's and patient's perspective) and the patients' preference with a highly efficacious and easy‐to‐use fixed combination of calcipotriol/betamethasone dipropionate topical gel after 8 weeks of once daily treatment in a large patient population. Methods In this phase IV, international, multicentre, randomized, controlled, prospective, parallel group study, adult patients with active, mild to moderate psoriasis despite previous topical psoriasis treatment, i.e. unsuccessful in the 8 weeks preceding study participation, are followed over 64 weeks. During the first 8 weeks the patients apply their medication once a day followed by a 56‐weeks maintenance period according to SmPC. Blinded interim analysis of all patients included demographics, Physician's Global Assessment, the novel Patient's self Global Assessment (PsGA) and Patient Preference Questionnaire (PPQ). Results 1795 patients were analysed. At week 8, 36.5% of the physicians rated the patients' psoriasis as clear/almost clear. Similarly, based on the patients' self‐assessment, 34.2% had a clear/almost clear score of PsGA in week 8. Analysis of the PPQ showed that the vast majority of the patients judged their 8‐week treatment to be preferable compared with their previous treatments. Conclusion Results of this blinded interim analysis indicate that the fixed combination of calcipotriol/betamethasone dipropionate gel is highly efficacious and preferred by the majority of analysed patients.